Genetic diversity and drug susceptibility patterns of the Mycobacterium tuberculosis complex in Yunnan, China. Issue 5 (31st May 2019) - Bai, Ruolan; Chi, Shuijing; Li, Xiaofei; Dai, Xiting; Ji, Zhenhua; Jian, Miaomiao; Bi, Yunfeng; Wang, Feng; Ding, Zhe; Luo, Lisha; chen, Taigui; Liu, Aihua; et al.
Abstract : Tuberculosis (TB) is an infectious disease caused by Mycobacterium tuberculosis (Mtb) which has been threatening global public health for many years. High genetic diversity is dominant feature of Mtb. Increasing cases of multidrug-resistant (MDR) tuberculosis (MDR-TB) is a serious public health problem to TB control in China. Spontaneous mutations in the Mtb genome can alter proteins which are the target of drugs, making the bacteria drug resistant. The purpose of the present study was to analyze the genotype of Mtb isolates from some areas in Yunnan, China and explore the association between genotypes and MDR-TB. Using spoligotyping, we identified Beijing genotypes, six non-Beijing genotypes and a number of orphan genotypes from 270 Mtb isolates from patients in Yunnan Province during 2014–2016. Of 270 Mtb isolates, 102 clinical Mtb strains were identified as drug-resistant (DR) by drug susceptibility testing (DST), among them, 52 MDR strains. Beijing genotypes occupied the highest MDR proportion (78.85%) followed by the orphan genotypes (15.38%). The characteristics of MDR strains showed high genetic diversity. The results will help to efficiently improve diagnosis and treatment and provide valuable information for Mtb molecular epidemiology.